2016
DOI: 10.1002/wat2.1154
|View full text |Cite
|
Sign up to set email alerts
|

Drought indicators revisited: the need for a wider consideration of environment and society

Abstract: Abstract[Drought indicators are proliferating, but with little consideration of which are most meaningful for describing drought impacts. A number of recent reviews compare different drought indicators, but none assess which indicators are actually used in the many operational drought monitoring and early warning efforts, why they were selected, or whether they have been 'ground-truthed', i.e., compared with information representing local drought conditions and/or impacts. Also lacking is a comprehensive asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
184
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 198 publications
(206 citation statements)
references
References 133 publications
2
184
0
Order By: Relevance
“…uio.no/edc/droughtdb/) collect and categorize textual drought impact reports, whereas Lackstrom et al (2013) and others suggest the development of a more targeted impact monitoring. A survey of operational monitoring and early warning systems by Bachmair et al (2016a) found that many regional systems do monitor impacts, however, not in a systematic way and thus they do not consider them for the drought warning and other management in a quantitative manner. Hence, impact monitoring is an important starting point for improvement.…”
Section: Impacts Of Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…uio.no/edc/droughtdb/) collect and categorize textual drought impact reports, whereas Lackstrom et al (2013) and others suggest the development of a more targeted impact monitoring. A survey of operational monitoring and early warning systems by Bachmair et al (2016a) found that many regional systems do monitor impacts, however, not in a systematic way and thus they do not consider them for the drought warning and other management in a quantitative manner. Hence, impact monitoring is an important starting point for improvement.…”
Section: Impacts Of Droughtmentioning
confidence: 99%
“…Figure 6 gives an overview of the different methods. The most widely adopted approach to relate drought indicators to impacts is to link commonly used hydrometeorological drought indicators to agricultural yield (Lobell et al, 2008;Vicente-Serrano et al, 2012Bachmair et al, 2016a). Most of these studies are based on correlation and as summarized by Stagge et al (2015a), thus are useful for screening relationships, but they measure the response of a variable, such as crop yield, across its entire range of values including typical or even productive years.…”
Section: Impacts Of Droughtmentioning
confidence: 99%
“…However, comparisons of spatiotemporal climate patterns over the formation, progression and termination of regional, multi-year WUS droughts remain scarce. Recent work offers substantive comparisons of droughts and effects, but these and similar studies can be spatially or temporally limited, or use indicators unsuited to assessing ecological impacts or longterm trends (Bachmair et al 2016, Robeson et al 2016, Ge et al 2016, Asner et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations in drought metrics are unavoidable: severity is subjective beyond "dry" (Alley 1984, Bachmair et al 2016. Stakeholder-specific thresholds identifying extreme aridity must be established, as drought indicators useful for one application may not be relevant to another (Hayes et al 2005, Stephenson 1998, Steinemann 2014, Bachmair et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This work contributes to a larger conversation among researchers, natural resources managers, and decision-makers globally about how to best conceptualize drought so that it can be better planned for and the impacts better mitigated. A recent review by Bachmair et al (2016) points to a significant gap between how drought is characterized by conventional drought indicators and how drought is experienced locally. They note that ''citizen science initiatives and other social learning approaches that explore drought framing.…”
Section: Resultsmentioning
confidence: 99%